Analyze of Customer Based Brand Equity on Customer Loyalty in Fast Food Restaurant at Batam City - Helna Febriana; Fendy Cuandra (Institute of Computer Science (IOCS), 2022)
This study explains factors that influence customer loyalty towards fast food restaurants in Batam City. Factors tested in this study are brand image, brand awareness, perceived quality, service quality and brand identification on customer loyalty mediate by customer satisfaction and customer based brand equity. This research use causal comparative and purposive sampling method which only selected respondent who live in Batam City and eat fast food. Questionnaires distribute through google form to collect respondents and get 360 respondent. Data processed using SmartPLS 3.0 software. The result research shows that brand image, brand awareness, service quality and perceived quality significantly affect customer loyalty while brand identification does not affecr customer satisfaction because consumers feels that consuming fast food due to their interest in fast food not because identification to customer social class.